The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1055/s-0032-1312585
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Follistatin and Myostatin Propeptide by Anabolic Steroids and Gender

Abstract: The purpose of this pilot study was to investigate the impact of training, anabolic steroids and endogenous hormones on myostatin-interacting proteins in order to identify manipulations of myostatin signalling. To identify whether analysis of the myostatin interacting proteins follistatin and myostatin propeptide is suitable to detect the abuse of anabolic steroids, their serum concentrations were monitored in untrained males, bodybuilders using anabolic steroids and natural bodybuilders. In addition, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Strikingly, our gene array analysis revealed that transcript levels of Mstn were reduced Ͼ6-fold in satARKO LA muscle, which was confirmed by quantitative real-time PCR, Western blot, and on orx and T and DHT supplementation in WT mice. This positive regulation of Mstn expression by androgens is in accordance with the lower serum Mstn levels recorded in female compared to male subjects (54) and the increase in serum Mstn concentration observed on T treatment of both young and older men (55). Androgen regulation of Mstn was not restricted to LA muscle, in line with previous rodent orx and androgen treatment studies (56 -58).…”
Section: Discussionsupporting
confidence: 90%
“…Strikingly, our gene array analysis revealed that transcript levels of Mstn were reduced Ͼ6-fold in satARKO LA muscle, which was confirmed by quantitative real-time PCR, Western blot, and on orx and T and DHT supplementation in WT mice. This positive regulation of Mstn expression by androgens is in accordance with the lower serum Mstn levels recorded in female compared to male subjects (54) and the increase in serum Mstn concentration observed on T treatment of both young and older men (55). Androgen regulation of Mstn was not restricted to LA muscle, in line with previous rodent orx and androgen treatment studies (56 -58).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, in a previous study in humans, we detected gender differences in myostatin propeptide and follistatin concentrations (Mosler et al. ). Also McMahon et al.…”
Section: Discussionmentioning
confidence: 99%
“…Smoke decreases myostatin levels, while it was not dependent on current PA, parathyroid hormone (PTH), testosterone, and 17β-estradiol (31,34). Pro-myostatin is not affected by menstrual cycle (35) and females have slightly lower levels compared to males (25). High plasma levels of myostatin were found in in rats with chronic kidney disease (CKD) (36) and in patients with chronic obstructive pulmonary disease (COPD) (37).…”
Section: Pre-analytical Factorsmentioning
confidence: 99%